Not so straightforward integral...

Calculus Level 3

Evaluate 2 x + 1 x x sin 1 x 2 1 x 2 d x \displaystyle \int \frac{2\sqrt{x} + \sqrt{\frac{1}{x} - x} \sin ^{-1}x} {2\sqrt{1-x^2}} dx .

If the above integral is of the form f ( x ) + C \displaystyle f(x) + C , then find f ( 1 ) f(1) . (round up to 2 decimals)

NOTE : f ( x ) f(x) is to be taken as the anti-derivative of the given integrand without adding any constant values. e.g. If the answer to the integral was sin x + C \sin x +C , you take f ( x ) = sin x f(x) = \sin x and NOT something like sin x + 1 , sin x + 2 \sin x + 1, \sin x + 2 , etc.


The answer is 1.57.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Patrick Corn
Sep 25, 2019

This simplifies to x 1 x 2 d x + sin 1 x 2 x d x . \int \frac{\sqrt{x}}{\sqrt{1-x^2}} \, dx + \int \frac{\sin^{-1} x}{2\sqrt{x}} \, dx. Integrating the second integral by parts with u = sin 1 x , d v = d x 2 x u = \sin^{-1} x, dv = \frac{dx}{2\sqrt{x}} gives x 1 x 2 d x + x sin 1 x x 1 x 2 d x = x sin 1 x + C . \int \frac{\sqrt{x}}{\sqrt{1-x^2}} \, dx + \sqrt{x} \sin^{-1} x - \int \frac{\sqrt{x}}{\sqrt{1-x^2}} \, dx = \sqrt{x} \sin^{-1} x + C. The problem as stated is ambiguous, since I could have gotten x sin 1 x + 1 + C \sqrt{x} \sin^{-1} x + 1 + C as well, but apparently I was meant to plug in 1 1 to x sin 1 x , \sqrt{x} \sin^{-1} x, which gives π / 2 1.57 . \pi/2 \approx \fbox{1.57}.

Suggestion: fix the problem by stipulating that f ( 0 ) = 0. f(0) = 0.

Again, I think the NOTE is not quite sufficient. I mean, consider the well-known example: 2 sin ( x ) cos ( x ) d x = sin 2 ( x ) + C = cos 2 ( x ) + C = 1 2 cos ( 2 x ) + C , \begin{aligned} \int 2 \sin(x) \cos(x) \, dx &= \sin^2(x) + C \\ &= -\cos^2(x) + C \\ &= -\frac12 \cos(2x) + C, \end{aligned} where each of those three functions doesn't have any "obvious" constant values added to it, although of course any pair of them differs by a constant. I still suggest you stipulate that f ( 0 ) = 0. f(0) = 0. Or, equivalently, change the integral to a definite integral, from 0 0 to 1. 1.

Patrick Corn - 1 year, 8 months ago

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...